PENERIMAAN KHALAYAK PADA KAMPANYE AUDIO VISUAL: ANALISIS RESEPSI IKLAN ANIES-SANDI PILGUB JAKARTA 2017 - Saputra, Muhammad Irawan; Fajar, Dewanto Putra; AR, Muhammad Fikri (Universitas Merdeka Malang, 2019)
Nowadays, industry and politicians often use audio visuals to package their messages on an advertisement. For example, the election of the Governor of DKI Jakarta, where one of the candidates uses a video campaign on YouTube. This media has been dominated by a juvenile audience that can be categorized as swing voters in political concepts. Therefore, this study aims to find out how audio visual campaigns can be accepted by swing voters. Researcher used the Reception Analysis method to see how the audience received media exposure. The results of this study indicate that Anies-Sandi campaign ads are interpreted as egalitarian by the audience, and are able to display SARA problems with the concepts of harmony and tolerance. However, the Anies-Sandi campaign ad does not have a clear message because the message that delivered is very conceptual. Keywords: Audio Visual Advertising, Reception Analysis, Political CampaignDOI:Â https://doi.org/10.26905/nomosleca.v5i2.3258